(untitled) (The Review of Diabetic Studies, 2024)
Background: Acute respiratory tract infections (ARTIs) significantly contribute to child morbidity globally. Vitamin D has a critical role in immune modulation, with deficiency linked to elevated possibility of respiratory infections. Aim: The purpose of this investigation is to conduct a systematic review and meta-analysis to define the influence that Vit D supplementation has on the possibility and frequency of ARTIs, specifically in kids. Methods: A meta-analysis and systematic review were done in line with PRISMA guidelines. PubMed, Web of Science, Cochrane Library, in addition Scopus have been searched for eligible investigations up to 2025. Randomized controlled trials and observational investigations involving children (≤18 years) that assessed vitamin D supplementation and reported ARTI outcomes were included. Main Findings: Four studies published between 2007 and 2025 have been involved. Baseline serum 25(OH)D concentrations were comparable among Vit D and control groups(mean difference 0.08; 95% CI −0.18 to 0.34; p = 0.54). Vit D supplementation didn’t significantly reduce the proportion of children experiencing ARTIs (RR 0.77; 95% CI 0.57–1.03; p = 0.07). However, a significant reduction in ARTI incidence (episodes per child per year) was observed in the Vit D group (mean variance −0.22; 95% CI −0.36 to −0.09; p = 0.001), despite substantial heterogeneity. Conclusion: Vit D supplementation doesn’t significantly decrease the overall possibility of experiencing ARTIs in kids but may reduce the frequency of infection episodes. Further large-scale, well-designed trials are required to detect optimal dosing strategies and target populations.